THE ASSIMILATION OF VARIOUS HABITATS IS A RESULT OF THE ADAPTIVE RADIATION OF MOLLUSKS. ECOLOGICAL RADIATION OF MOLLUSKS IN NUTRITIONAL PROCESSES - SWAMI PRIYA (International Journal of Multidisciplinary Research and Studies, 2020)
The importance of fish as a valuable source of protein for human population has indeed been realised and hence rated high for its nutritional value. Fishery biologists often calculate condition factor to determine not only the health status of fish but also advise / suggest the time of harvesting of fish for human consumption. While it is impossible to enrich / enhance the quality of food of marine fish in the wild condition, for fresh water species, especially those which are reared, it is often possible to enrich the feed in order to have impact on the nutritional status of the fish for human consumption. Knowledge of the food and feeding habits of fishes of any water body is thus a prerequisite to improve its fishery potential as also to any program of fishery management. Study of the any program of fishery management. Study of the food and feeding habits of fishes therefore had attracted the attention of fishery biologists almost from the beginning of the present century.